Teaching Beauty in DeLillo, Woolf, and Merrill - Green-Lewis, J. author. aut Link
XVIII, 200 p.
Keywords: What happened to beauty? How did the university literature classroom turn into a seminar on politics? Focusing on such writers as Don DeLillo, Virginia Woolf, and James Merrill, this book examines what has been lost to literature as a discipline, and to literary criticism as a practice, as a result of efforts to reduce the aesthetic to the ideological. Green-Lewis and Soltan celebrate the return of beauty as a subject in its own right to literary studies, a return all the more urgent given beauty s ability to provide not merely consolation but a sense of order and control in the context of a threatening political world.